THE PSYCHOMETRIC PROPERTIES OF UPPER EXTREMITY FUNCTION TESTSIMPLIFIED VERSION IN HEALTHY YOUNG ADULTS. - Eyolcu, Aylin Tanrıverdi; Özcan, Ayşenur; Savcı, Sema (Karya Journal of Health Science, 2025)
Objective: The psychometric properties of the Upper Extremity Function Test-Simplified Version (UEFT-S) in healthy young adults are unknown. The objective of this study was to investigate the validity, test-retest reliability, and minimal detectable change of UEFT-S in healthy young adults. Method: Thirty-seven healthy individuals were recruited for our cross-sectional study. UEFT-S was utilised to assess upper extremity function. UEFT-S was administered twice, separated by one week, to evaluate test-retest reliability. To determine convergent validity, upper extremity muscle strength, handgrip strength, and upper extremity muscle activation were assessed using a handheld dynamometer, a hydraulic hand dynamometer and a surface electromyography, respectively. The test-retest reliability was determined using the intraclass correlation coefficient (ICC). Convergent validity was examined by Pearson's correlation coefficients or Spearman's rank-order correlation coefficients in accordance with the normal distribution. Results: UEFT-S demonstrated good test-retest reliability, evidenced by an ICC of 0.86 (95% Confidence Interval:0.73-0.93). The minimal detectable change was 5.65. UEFT-S score was significantly correlated with dominant shoulder flexor (r=0.492, p=0.002), shoulder abductor (r=0.340, p=0.039), elbow flexor (r=0.579, p<0.001), elbow extensor (r=0.566, p<0.001), and handgrip strength (r=0.421, p=0.009). A significant correlation was found between the UEFT-S score and percentage of maximum voluntary isometric contraction values of the anterior deltoid (r=- 0.586, p<0.001), middle deltoid (r=-0.485, p=0.002), biceps brachii (r=-0.475, p=0.003), and triceps brachii (r=-0.371, p=0.024). Conclusion: UEFT-S is a valid and reliable tool for assessing upper extremity function in healthy young adults. UEFT-S should be repeated at least twice to account for the learning effect. Higher UEFT-S scores are associated with greater upper extremity muscle strength and lower upper extremity muscle activation.